THE RELATIONSHIP OF RISK FACTORS WITH THE INCIDENT OF PEDICULOSIS CAPITIS IN CHILDREN OF SEKOLAH DASAR NEGERI 7 PEMECUTAN, DENPASAR CITY - Daniswara, Ida Bagus; Diarthini, Ni Luh Putu Eka; Swastika, I Kadek; Laksemi, Dewa Ayu Agus Sri (E-Jurnal Medika Udayana, 2025)
The incidence of pediculosis capitis is quite high throughout the world, so this disease has become a health problem in developed and developing countries, including Indonesia. This research uses analytical methods with a cross-sectional approach. Data was collected using a questionnaire and in conjunction with a head examination to determine if the subject was positive or negative for pediculosis capitis. The data collection technique used in this research was random sampling. Research data was analyzed bivariate using the chi-square statistical test and multivariate with binary logistic regression analysis. The prevalence of pediculosis capitis at SDN 7 Pemecutan was 48 out of 122 people (39.3%). Risk factors associated with the incidence of pediculosis capitis include gender ( p <0.05), hair length ( p <0.05), use of shared combs or accessories ( p <0.05), and contact with people who are infested ( p <0.05). Meanwhile, risk factors that are not related to the occurrence of pediculosis capitis infestation are age ( p > 0.05), frequency of hair washing ( p > 0.05), and use of shared beds or pillows ( p > 0.05). The risk factor that most influence cases of pediculosis capitis is the use of combs and accessories together. Keywords: Pediculosis capitis, prevalence, risk factors